Precambrian-Cambrian trace fossils from the Yangtze Platform (South China) and the early evolution of bilaterian lifestyles - Weber, B.; Steiner, M.; Zhu, M. -Y. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2007)
Siliciclastic, carbonaceous and phosphoritic shallow marine sediments from several Neoproterozoic (Ediacaran) and Precambrian-Cambrian (PC-C) boundary sections on the Yangtze Platform, South China contain remarkable trace fossil assemblages. The present paper provides a general overview on the distribution and the possible palaeobiological and palaeoenvironmental significance of these trace fossil assemblages from selected PC-C boundary sections on the passive Yangtze Platform margins. Comparative investigations of the typology of Neoproterozoic (Ediacaran) ichnofaunas as well as of the related sedimentary enviromnents accompanying the ichnoassemblages demonstrate in general correspondence with other studies worldwide that the Neoproterozoic ichnofaunas are mainly composed of slightly curved to straight and unbranched horizontal traces, which are usually related to the occurrence of shallow marine softgrounds scaled by microbial mats. Rare traces show ichnomorphological patterns that indicate developments toward a more effective horizontal exploitation of the feeding ground during the late Neoproterozoic and earliest Cambrian. The majority of these traces appear to represent undermat miners with simple feeding strategies. During the earliest Phanerozoic (early Meishucunian Stage, equivalent to the Nemakit-Daldynian Stage of Siberia), the oxic shallow-water environments along the ancient continental passive margins of the Yangtze platform were populated by large, as yet unknown arthropods which produced Rusophycus-type trace fossils. The late Precambrian to early Phanerozoic sediments of the Yangtze Platform generally provide excellently preserved trace fossil records, which together with the presence of index fossils (SSF) from the Nemakit-Daldynian Stage, provide a more detailed insight into the development of PC-C palaeoenvironments and the evolution of lifestyles among early bilaterian metazoans. A preliminary comparison of the Neoproterozic biotas occurring on the Yangtze Platform and in other ...